Neuroimaging in non-accidental head injury in children: an important element of assessment. Issue 1027 (30th March 2011) - Rajaram, S; Batty, R; Rittey, C D C; Griffiths, P D; Connolly, D J A
Abstract : Head injury from physical abuse is unfortunately a common occurrence in our society. It is a major cause of mortality and long-term physical and psychological disability in children. Diagnosis of non-accidental head injury may be difficult, as most infants present with non-specific clinical findings and without external signs of trauma. Neuroimaging plays a fundamental role both for medical management and medicolegal aspects of child abuse. It is therefore imperative for the radiologist to promptly recognise the radiological findings of various forms of non-accidental head injury to render a more accurate opinion. A standardised imaging protocol and good communication between professionals are essential for optimum management.